Social Class and Capital Punishment: A Theoretical and Empirical Analysis - Tilley, Jennifer L. (2014)
While it is generally assumed that virtually all persons executed in the United States are poor, the social class - execution link has not been well documented or theorized in the literature. Far more research has analyzed the relationship of race and gender to execution. Using data on executions carried out in Texas between 2000 and 2012, individuals sentenced to death from the Supreme Court's Gregg decision through 1997 in Tennessee, narrative case studies, and a content analysis of state-defined mitigating circumstances, this study provides both detailed documentation of the social class characteristics of those executed, as well as a theoretical account of the social class - capital punishment relationship. By drawing on the works of scholars such as Bourdieu, Kaplan, Haidt, Bandura, and Black, an integrated framework for conceptualizing the manner in which social class conditions capital decision making across various points of the legal process is presented. Succinctly stated, the theoretical model used to explain this relationship contends that the death penalty functions as part of a wider ideological system of power and social control. Sporadic death sentences prop up ideological imagery of justice and safety without representing the state as unduly repressive, and thus allow expendable others (i.e., the poor) to become scapegoats for the continuance of a system of subjugation. Essentially, capital punishment is influential in shaping hegemonic ideology that, in perpetuating harsh treatment of the poor, reinforces class stratification amidst claims of egalitarianism. Therefore, the analysis implies that social class bias should receive attention in capital punishment debate commensurate with issues such as race, gender, age, and mental functioning